Marketing Public Relations Activities in Building Local Media Brand Positioning in the Renewable Media Era - Indriastuti, Dwi Cahyanti; Tunggali, Ade Putranto Prasetyo Wijiharto (Universitas Muhammadiyah Yogyakarta, 2023)
Public Relations in a company or institution can be achieved through Marketing Public Relations in order to achieve certain targets which previously had to have a clear and detailed work program. Marketing public relations is effective in building brand (product) awareness as well as brand knowledge. Marketing public relations is considered effective, the role of marketing public relations is needed to market a product or program with creative ideas. This study aims to find out about marketing public relations activities in building brand positioning using push, pull and pass strategies. In its development, in the digital era as it is today, many print media have gone out of business. One of the print media that has gone out of business (closed publication) is Republika, which will end at the end of 2022. Unlike Harian Jogja, which is still able to maintain its print media amidst the onslaught of technology. In more detail, the purpose of this study is to examine marketing public relations activities in building local media brand positioning in the era of renewable media. This research uses a qualitative approach, and Harian Jogja as the subject of study. Data collection techniques through observation, interviews and documentation. Marketing Public Relations activity is a step or method that every company takes in building a company's Brand Positioning. The Result for Marketing Public Relations activities have a very important role in making a brand progress and developing or the ability to market products and the superior quality of a company to the audience. One of the activities that can build the Harian Jogja Brand Positioning is the existing promotional programs and feedback from customers who always provide motivation and existing complaints. With the promotions, and feedback provided by Harian Jogja, it is able to give an attractive impression to customers through the strategies implemented.